Analisis Pengaruh Rasio Kompresi Dan Persentase Etanol Pada Bahan Bakar Terhadap Kinerja Mesin Otto 4 Langkah - Faizal Akbar; Santoso Santoso (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The public demand for better vehicle performance is increasing. Increasing the compression ratio and fuel octane is one solution to improve vehicle performance. This study aims to determine the effect of increasing the compression ratio and ethanol mixture in fuel on the power and torque of the 125 cc Otto engine. The method used is an experiment using a dynotest. The compression ratio was varied to 8.9, 9.2, and 9.6, with ethanol mixtures of 5%, 10%, and 15%. The test data were analyzed using the two-way ANOVA method. The results showed that increasing the compression ratio and ethanol mixture can increase engine power and torque. The highest peak power and torque occurred at a compression ratio of 9.6 with 15% ethanol, which was 6.11 kW and 10.23 N.m. A compression ratio of 9.2 produces 6.07 kW of power and 10.07 N.m of torque at 15% ethanol. A compression ratio of 8.9 produces 5.62 kW of power at 15% ethanol and 9.73 N.m of torque at 10% ethanol.